The N-mannosyltransferase MoAlg9 plays important roles in the development and pathogenicity of Magnaporthe oryzae - Shulin Zhang; Yu Wang; Jinmei Hu; Xinyue Cui; Xiaoru Kang; Wei Zhao; Yuemin Pan (Journal of Integrative Agriculture)
Magnaporthe oryzae is the causal agent of rice blast. Glycosylation plays key roles in vegetative growth, development, and infection of M. oryzae. However, several glycosylation-related genes have not been characterized. In this study, we identified a Glyco_transf_22 domain-containing protein, MoAlg9, and found that MoAlg9 is localized to the endoplasmic reticulum (ER). Deletion of MoALG9 significantly affected conidial production, normal appressorium formation, responses to stressors, and pathogenicity of M. oryzae. We also found that the ΔMoalg9 mutant was defective in glycogen utilization, appressorial penetration, and invasive growth in host cells. Moreover, we further demonstrated that MoALG9 regulates the transcription of several target genes involved in conidiation, appressorium formation, and cell wall integrity. In addition, we found that the Glyco_transf_22 domain is essential for normal MoAlg9 function and localization. We also provide evidence that MoAlg9 is involved in N-glycosylation pathway in M. oryzae. Taken together, these results show that MoAlg9 is important for conidiation, appressorium formation, maintenance of cell wall integrity, and the pathogenesis of M. oryzae.